Psycho-social factors associated with the nationwide lockdown in India during COVID- 19 pandemic - Nilima Nilima; Siddharth Kaushik; Bhaskar Tiwary; Piyush Kant Pandey (Elsevier, 2021)
Objective: To investigate the psycho-social factors associated with COVID-19 and the nationwide lockdown in India. Study design: An online survey was conducted from April 11 through April 16, 2020 in 28 states and 8 union territories (UT) of India. The potential participants were recruited using snowball sampling procedure. Methods: A cross-sectional online survey was conducted among the people of all states in India. A spatial analysis was performed and Moran's I statistic was applied to investigate the overall clustering of locations. Fisher's exact test was used to investigate associations. GeoDa and R console were used to analyze the data. A total of 1316 responses were received. Results: Those worried for their family's health were likely to follow the lockdown measures(p<0.001).Significant association was observed (p<0.001) between following the lockdown measures and being satisfied with the government strategy to combat the COVID-19 pandemic. A significant relation was observed between the gender (p = 0.001), job profile (p<0.001) and physical activity (p<0.001) were observed to be associated with the psycho-social impact. Conclusion: Government and public health officials should consider the sentiments of the community while planning strategies relating to the pandemic. The findings of this study will assist the policymakers in emphasizing the psychological well-being of individuals, along with physical health.